2020
DOI: 10.1182/bloodadvances.2020001675
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of HTLV-1 expression by the HBZ RNA through interference with the basal transcription machinery

Abstract: Key Points By disrupting basal transcription machinery, HBZ RNA inhibits sense transcription of human T-cell leukemia virus type 1. Repression of genomic expression may allow entry into proviral latency and escape from immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…It has been previously suggested that HBZ mRNA plays a role in supporting proliferation of ATL cells ( 16 ). The rather unexpected nuclear compartmentalization of HBZ mRNA ( 40 ), confirmed and extended in a recent investigation ( 41 ) gives further support to the notion that HBZ mRNA is acting as a transcriptional modulator not only of the viral genome, where it may participate to viral latency ( 42 ), but also of host gene expression ( 16 , 41 , 43 ). Within this frame, HBZ mRNA behaves therefore as a bifunctional molecule with coding capacity and regulatory properties ( 44 ).…”
Section: Future Directionssupporting
confidence: 68%
“…It has been previously suggested that HBZ mRNA plays a role in supporting proliferation of ATL cells ( 16 ). The rather unexpected nuclear compartmentalization of HBZ mRNA ( 40 ), confirmed and extended in a recent investigation ( 41 ) gives further support to the notion that HBZ mRNA is acting as a transcriptional modulator not only of the viral genome, where it may participate to viral latency ( 42 ), but also of host gene expression ( 16 , 41 , 43 ). Within this frame, HBZ mRNA behaves therefore as a bifunctional molecule with coding capacity and regulatory properties ( 44 ).…”
Section: Future Directionssupporting
confidence: 68%
“…HBZ plays important roles in the proliferation and survival not only of ATL cells but also of infected nonleukemic cells. We and others have reported the distinct functions of HBZ protein and HBZ RNA (Gazon et al, 2020; Mitobe et al ., 2015; Satou et al ., 2006). RNAs imbued with both coding and non-coding functions are known to exist in bacteria, plants, and animals and are referred to as “bifunctional RNAs” or “coding and non-coding RNAs (cncRNAs)” (Sampath and Ephrussi, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…HBZ mRNA promotes the proliferation of T cells and enhances transcription of anti-apoptotic genes including survivin (46). Furthermore, HBZ mRNA interferes with the basal transcription machinery, leading to suppression of sensetranscription from the LTR (49). It is reported that HBZ protein also suppresses sense-transcription from the LTR (11).…”
Section: Function Of Hbzmentioning
confidence: 99%
“…It is reported that HBZ protein also suppresses sense-transcription from the LTR (11). Thus, both HBZ mRNA and protein are involved in the suppression of sense transcription of viral genes (11,49). Viral proteins that are encoded in the plus strand are well-recognized by CTLs.…”
Section: Function Of Hbzmentioning
confidence: 99%